10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Modern lifestyles increasingly promote unhealthy eating behaviors, contributing to the global rise in cardiovascular-kidney-metabolic diseases (CKMD). Circadian rhythms, anticipatory responses that coordinate biological processes with the 24-hour rotation of the earth, are tightly linked to feeding behavior and nutrient metabolism, which are crucial for cardiovascular-kidney-metabolic homeostasis. At the molecular level, core circadian "clock genes" take part in a highly-conserved, regulatory feedback loop that optimizes metabolic processes for the anticipated time of food intake. Among the molecular components of the circadian clock, the transcription factor brain and muscle aryl hydrocarbon receptor nuclear translocator-like 1 (BMAL1) plays a central role in coordinating metabolic functions. Notably, BMAL1 and feeding behavior are at the intersection of circadian biology and metabolism regulating each other. In this review, we summarize recent insights in metabolic physiology from global and tissue-specific Bmal1 knockout animal models, highlighting how BMAL1 influences CKMD consequences in response to dietary composition, feeding schedules, and whether sex is a determinant in these outcomes. We also discuss the potential of molecular clock-targeted therapies for CKMD. Maintaining circadian integrity is central to mitigating CKMD. Thus, suggesting that modulating clock-regulated pathways may offer novel therapeutic strategies.